2016
DOI: 10.1175/waf-d-15-0161.1
|View full text |Cite
|
Sign up to set email alerts
|

The Origin of Western European Warm-Season Prefrontal Convergence Lines

Abstract: The authors investigate the origin of prefrontal, warm-season convergence lines over western Europe using the Weather Research and Forecasting Model. These lines form east of the cold front in the warm sector of an extratropical cyclone, and they are frequently the focus for convective development. It is shown that these lines are related to a low-level thermal ridge that accompanies the base of an elevated mixed layer (EML) plume generated over the Iberian Peninsula and northern Africa. Using Q-vector diagnos… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 65 publications
0
7
0
Order By: Relevance
“…This is in agreement with the findings of Catto and Pfahl [] who note that extreme‐precipitation‐producing fronts have up to 35% stronger frontal strengths. This implies that an increase in the number of extremely strong fronts (Figures and ) potentially is one driving agent behind an increase in the number of extreme precipitation events, in particular, because summertime convective thunderstorms frequently form in prefrontal zones [ Browning and Monk , ; van Delden , , ; Dahl and Fischer , ].…”
Section: Discussion: Frontal Strength and Implications For Frontal Prmentioning
confidence: 99%
“…This is in agreement with the findings of Catto and Pfahl [] who note that extreme‐precipitation‐producing fronts have up to 35% stronger frontal strengths. This implies that an increase in the number of extremely strong fronts (Figures and ) potentially is one driving agent behind an increase in the number of extreme precipitation events, in particular, because summertime convective thunderstorms frequently form in prefrontal zones [ Browning and Monk , ; van Delden , , ; Dahl and Fischer , ].…”
Section: Discussion: Frontal Strength and Implications For Frontal Prmentioning
confidence: 99%
“…A similar concern regarding the lack of similarity in θ and θ e for frontal analysis has been noted by Heimann (1992) in the case of a prefrontal foehn. The western European prefrontal convergence lines associated with north African air masses (Dahl and Fischer 2016) may also have this behavior, although maps of surface θ e were not presented. Thus, in some situations where the prefrontal air is particularly dry (illustrated here with situations from the Great Plains and prefrontal foehn, but not limited to those), using θ e in frontal analyses might misrepresent the situation.…”
Section: Petterssen Frontogenesismentioning
confidence: 99%
“…As an example, thunderstorms in Western Europe are often characterized by a circulation type that features an upstream synoptic-scale trough that brings low-level moisture northward (van Delden 2001). This layer of air is initially capped by an elevated mixed layer with high instability until a front or a prefrontal convergence line produces the required lift to initiate storms (van Delden 1998, Dahl and Fischer 2016, Schemm et al 2016. In studies of severe weather events across Europe, the synoptic scale was found to be important in providing the required atmospheric moisture, e.g.…”
Section: Introductionmentioning
confidence: 99%